Register Pertanian di Kecamatan Wonosalam Kabupaten Demak - Zulfa, Ilma (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2024)
Register is a variety of language that is seen based on the context of use. As in the agricultural register. Agricultural activities contain a variety of vocabulary that is unique to research. The purpose of this study is to discuss the form, meaning and social factors of agricultural registers in Wonosalam District, Demak Regency. The theory used is register according to Halliday and Biber. Data sources were obtained through interviews and literature studies. There are 36 data of agricultural registers in Wonosalam Subdistrict, Demak Regency which consist of noun words and verb words. The social factors of agricultural register formation are economy, education, age and population mobility.Keywords: register, agriculture, Demak.